2018
DOI: 10.1002/cpdd.641
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a High‐Fat Meal on the Pharmacokinetics of Brigatinib, an Oral Anaplastic Lymphoma Kinase Inhibitor, in Healthy Volunteers

Abstract: Brigatinib, a next‐generation anaplastic lymphoma kinase (ALK) inhibitor, received accelerated approval in the United States for the treatment of patients with metastatic ALK+ non–small‐cell lung cancer who have progressed on or are intolerant to crizotinib. A clinical study was conducted to assess the effect of food on brigatinib pharmacokinetics (PK). Healthy subjects received a single oral dose of brigatinib 180 mg (2 × 90‐mg tablets) after a 10‐hour fast or after a high‐fat meal in a 2‐period, 2‐sequence c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 24 publications
0
35
0
Order By: Relevance
“…34 During food-effect studies, the brigatinib AUC and C max were reduced by 2% and 13%, respectively, in healthy subjects when administered with a high-fat meal (920 calories, 58 grams carbohydrate, 59 grams fat and 40 grams protein). 43 Therefore, patients were instructed to take brigatinib without regard to meals. 20…”
Section: Brigatinibmentioning
confidence: 99%
“…34 During food-effect studies, the brigatinib AUC and C max were reduced by 2% and 13%, respectively, in healthy subjects when administered with a high-fat meal (920 calories, 58 grams carbohydrate, 59 grams fat and 40 grams protein). 43 Therefore, patients were instructed to take brigatinib without regard to meals. 20…”
Section: Brigatinibmentioning
confidence: 99%
“…2 The recommended dose of brigatinib is 90 mg orally once daily for the first 7 days of treatment, which, if tolerated, is followed by escalation to 180 mg once daily. 5 Therefore, brigatinib can be administered with or without food. 3 After administration of 180 mg brigatinib once daily in patients with cancer, the mean plasma elimination half-life was 25 hours, with a corresponding steady-state apparent oral clearance (CL/F) of 12.7 L/h.…”
mentioning
confidence: 99%
“…Brigatinib single-and repeat-dose systemic exposures increased dose-proportionally following administration in patients with cancer across the dose range of 60-240 mg once daily. 5 Following administration of a single 180-mg oral dose of [ 14 C]-brigatinib to healthy volunteers, 65% and 25% of the administered dose were recovered in feces and urine, respectively. 3,4 A study in healthy volunteers demonstrated that consumption of a high-fat meal decreased brigatinib peak concentration (C max ) by 13% and delayed median time to C max (t max ) from 2 hours to 5 hours compared with fasted-state administration, but it had no impact on total systemic exposure.…”
mentioning
confidence: 99%
See 2 more Smart Citations